Evaluasi Sistem Penyimpanan Sediaan Farmasi Berdasarkan Standar Pelayanan Kefarmasian Rumah Sakit dan Syariat Islam di RSI Sultan Agung Semarang: Evaluation of the Pharmaceutical Preparation Storage System Based on Hospital Pharmaceutical Service Standards and Islamic Sharia at RSI Sultan Agung Semarang - Zulfitri; Yanna Sagitasari; Atina Hussana (Universitas Ngudi Waluyo, 2024)
Pharmaceutical services are the main maintenance services for a hospital. RSI Sultan Agung Semarang is a hospital that has been certified according to Islamic law and has pharmaceutical installations, especially pharmaceutical logistics, which are responsible for pharmaceutical preparations, medical devices and consumable medical materials to avoid damage and maintain the quality of pharmaceutical preparations. The aim of this research is to determine the harmony of the spatial layout and storage system for pharmaceutical preparations at the Pharmacy Logistics RSI Sultan Agung Semarang based on the Standard Instructions for Pharmaceutical Services in Hospitals and Islamic Sharia. This descriptive observational research method uses prospective data collection techniques in the February-March period through interviews with the pharmacist in charge of the pharmacy warehouse. The data taken includes the spatial layout and storage system for pharmaceutical preparations and the data acquisition score is calculated using the Guttman scale. The results of data analyzed descriptively show that there is a balance in the spatial planning checklist of 94.75% (very good) and a storage system of 90.91% (very good) and conformity based on Islamic law of 25% (not good). The storage system for pharmaceutical preparations in pharmaceutical logistics at RSI Sultan Agung Semarang is based on pharmaceutical service standards in hospitals and Islamic law with an average percentage of 70.22% in the (good) category. ABSTRAK Pelayanan kefarmasian merupakan pelayanan penunjang utama bagi suatu rumah sakit. RSI Sultan Agung Semarang merupakan rumah sakit yang telah tersertifikasi secara syariat Islam dan memiliki Instalasi farmasi khususnya farmasi logistik yang bertanggung jawab terhadap sediaan farmasi, alat kesehatan, dan bahan medis habis pakai agar tetap terhindar dari kerusakan serta menjaga mutu sediaan farmasi. Tujuan penelitian ini adalah untuk mengetahui kesesuaian tata ruang dan sistem penyimpanan sediaan farmasi di logistik farmasi RSI Sultan Agung Semarang berdasarkan Petunjuk Standar Pelayanan Kefarmasian di Rumah Sakit dan Syariat Islam. Metode penelitian observasional deskriptif ini menggunakan teknik pengumpulan data secara prospektif pada periode Februari-Maret melalui wawancara kepada Apoteker Penanggung Jawab logistik farmasi. Data yang diambil meliputi tata ruang dan sistem penyimpanan sediaan farmasi. Skor perolehan data dihitung menggunakan skala guttman. Hasil data yang diperoleh dianalisis secara deskriptif menunjukkan bahwa terdapat kesesuaian ceklist tata ruang sebesar 94,75 % (sangat baik) dan sistem penyimpanan sebesar 90,91 % (sangat baik) serta kesesuaian berdasarkan syariat Islam sebesar 25 % (kurang baik). Sistem penyimpanan sediaan farmasi di logistik farmasi di RSI Sultan Agung Semarang berdasarkan standar pelayanan kefarmasian di Rumah Sakit dan syariat Islam dengan hasil rata-rata presentase sebesar 70,22 % masuk dalam kategori (baik).